GANTI RUGI TERHADAP KORBAN KECELAKAAN LALU LINTAS YANG MENGALAMI CACAT FISIK DI TINJAU DARI ASPEK HUKUM PERDATA - Khairunnisah, Nanda Theresia dan (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2019)
Legal rules often focus on punishing criminals but victims also need to be considered because victims are the parties who are sufficiently disadvantaged and suffer. Everyone thinks that the best way to help the victim is to catch the criminal, as if the criminal is the only source of trouble for the victim in the traffic accident. This is the background of the author taking the title Compensation Against Traffic Accident Victims Who Have Physical Disabilities In Review Of Civil Aspects. The method used in this study is normative legal research. Conclusions from the formulation of the problem taken in terms of compensation efforts based on Article 1365 of the Civil Code reads "Every act that violates the law, which brings harm to others, requires people who due to their wrongdoing to repay these losses" and based on research located in the Regency The results of the Kutai Kartanegara are that the number of traffic accidents that occur during 2017 to 2019 is a problem that often occurs on the road and is unavoidable because traffic accidents are unpredictable. Law Number 22 of 2009, Article 229 states that; Traffic Accidents are classified as: Light traffic accidents, Medium traffic accidents and Heavy traffic accidents. Presumably the government can make special laws and regulations regarding the problem of compensation for victims who experience physical or non-physical disabilities.